Development of a novel forming tool for the production of high-strength aluminum components with tailored properties - Rigas, Nikolaos; Merklein, Marion (IOP Conference Series: Materials Science and Engineering, 2024)
Because of growing environmental and technical requirements, the efficient manufacturing of components with tailored properties using recyclable materials is mandatory. The combination of high-strength aluminum alloys and thermal-assisted forming operations is an innovative method for the production of components with varying mechanical properties. By locally adjusting the cooling rates during a thermo-mechanical forming operation, it is possible to modify the microstructure and precipitation conditions. A subsequent aging operation causes different microstructural and mechanical characteristics. This allows both deep-drawing and adjustment of the component properties in one single step. For this reason, this contribution focuses on the production of components with tailored properties. With the aid of a non-contact measuring system, previous investigations have proved that mechanical material properties can be adapted during a forming process by adjusting the cooling rates. In this contribution, this knowledge is transferred to a novel temperature-controlled rectangular cup tool. A variation of the local tool temperature and holding duration in the tool will be carried out. Then, the mechanical and microstructural properties of the manufactured components will be characterized through hardness and DSC investigations. In addition, the influence of different tool temperatures on the component temperature, the sheet thickness distribution and process forces will be investigated. As a result, it has been demonstrated that mechanical, process-related and geometric advantages can be achieved by using locally temperature-controlled forming tools.<br